2020
DOI: 10.1371/journal.pone.0243359
|View full text |Cite
|
Sign up to set email alerts
|

Comparative intra-articular gene transfer of seven adeno-associated virus serotypes reveals that AAV2 mediates the most efficient transduction to mouse arthritic chondrocytes

Abstract: Osteoarthritis (OA) is the most common arthropathy, characterized by progressive degeneration of the articular cartilage. Currently, there are no disease-modifying approaches for OA treatment. Adeno-associated virus (AAV)-mediated gene therapy has recently become a potential treatment for OA due to its exceptional characteristics; however, the tropism and transduction efficiency of different AAV serotypes to articular joints and the safety profile of AAV applications are still unknown. The present study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Extensive works have highlighted the role of IL‐1β in the development of OA and the involvement of nod‐like receptor protein‐3 (NLRP3)‐mediated inflammasome in promoting various joint compartments has garnered significant attention. Both in vitro and in vivo OA model experiments conducted by our team and other researchers have consistently demonstrated that aberrant activation of NF‐κB signalling leads to crucial activation of caspase‐1‐mediated pyroptosis, which drives chondrocyte pyroptosis in OA pathogenesis 10–14 . Moreover, subchondral bone and articular cartilage act together not only mechanically but biologically to accelerate OA progression 15 .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Extensive works have highlighted the role of IL‐1β in the development of OA and the involvement of nod‐like receptor protein‐3 (NLRP3)‐mediated inflammasome in promoting various joint compartments has garnered significant attention. Both in vitro and in vivo OA model experiments conducted by our team and other researchers have consistently demonstrated that aberrant activation of NF‐κB signalling leads to crucial activation of caspase‐1‐mediated pyroptosis, which drives chondrocyte pyroptosis in OA pathogenesis 10–14 . Moreover, subchondral bone and articular cartilage act together not only mechanically but biologically to accelerate OA progression 15 .…”
Section: Introductionmentioning
confidence: 62%
“…Both in vitro and in vivo OA model experiments conducted by our team and other researchers have consistently demonstrated that aberrant activation of NF‐κB signalling leads to crucial activation of caspase‐1‐mediated pyroptosis, which drives chondrocyte pyroptosis in OA pathogenesis. 10 , 11 , 12 , 13 , 14 Moreover, subchondral bone and articular cartilage act together not only mechanically but biologically to accelerate OA progression. 15 Emerging evidence reveals that subchondral bone lesions, including angiogenesis and sensory neuron ingrowth, are responsible for cartilage sabotage and pain.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed that AAV2 and AAV6.2 could effectively deliver therapeutic genes into human joint tissues. Others have reported that AAV2 has the highest transduction efficiency in the cartilage of knee joints 19 , it has been used in clinical trials in patients with inflammatory arthritis. 20 Collectively, these studies support the current data that AAV2 is one of the most efficient vector systems with which to transfer therapeutic genes into chondrocytes of human joint cartilage.…”
Section: Discussionmentioning
confidence: 99%
“… Data compiled from (Refs. 3 , 8 , 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ). Superscript letters: h, human; c, canine; I, pig; m, murine; p, non-human primate; r, rat; s, sheep.…”
Section: Aav Capsidsmentioning
confidence: 99%
“… Data compiled from (Refs. 3 , 8 , 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ). …”
Section: Aav Capsidsunclassified